English Deixis in Picture Storybooks for Children - Allyda Ulfa Nafi'ah; Rohmani Nur Indah; Toyyibah Toyyibah (Wanastra: Jurnal Bahasa dan Sastra, 2021)
Deictic expression is a noticeable item in linguistic studies to recognize the meaning of a specific context. Thus, pragmatic analysis in this research is to find five kinds of deixis those are: personal deixis (first, second, and third person deixis), place deixis, time deixis, social deixis and discourse deixis. The theory that is used in this research is the theory of deixis by Levinson (1983). The present study investigates the use of Deictic expression in five children picture storybook. The titles of each book are Reba wants ice cream, Gappu can't dance, Bunty and Bubbly, A new pet in the family, and under my bed. In this research, the researcher conducted a descriptive qualitative research. From two research problem of this study What types of deixis found in the children's story books? And what are the patterns of the Deixis types in children's storybooks? the researchers found that in all story books, personal deixis is the most identifiable type of deixis. Some pattern of the Deixis types in Children's storybooks like the word; I, now, there, this, mother was found in the sentences of the story.  Key words: deixis, picture storybook, pragmatics